You ought to! : a psychoanalytic study of the superego and conscience - Barnett, Bernard R. (Psychoanalytic ideas., 2007)
The superego is one of those psychoanalytic concepts that has been assimilated into ordinary language, like repression, the unconscious and the Oedipus complex. Because it has become such a familiar notion, its complexity may not always be appreciated, nor the controversy that it can inspire. Its origins, for example, its timing in the course of development, whether and how it is influenced by gender all these questions and others have been the source of lively disagreement. For psychoanalysts it is a fundamental concept of their discipline, but it belongs to a meta psychology whose value is o.